Donasi Sosial Lintas Agama: Tinjauan Fiqh Muamalah dalam Pengabdian Mahasiswa HES - Mhd. Dzaky Ramadhan; Lia Adetia Harahap; Mei Purnama Sari; Rafika Shahira Adisty; Siti Rahayu; Zaldy Ichsan Febrian (Getpress Management Journals, 2025)
This article discusses the practice of hibah (voluntary giving) in interfaith social donations carried out by students of Islamic Economic Law (HES) as part of a community service program. The main focus lies in how the concept of hibah in fiqh muamalah can be applied within the context of multicultural social life, particularly in Indonesia, which is known for its religious diversity. This study employs a descriptive qualitative method with a field study approach, in which students directly participated in interfaith donation activities at the community level. The findings reveal that hibah, as a form of voluntary giving, can serve as a medium of da‘wah bil hal (preaching through action) while simultaneously strengthening social relations among people of different faiths. The article further emphasizes that fiqh muamalah is not only relevant in the field of economic transactions but also plays a significant role in fostering social harmony through the instrument of hibah.